THE EFFECT OF USING SONG LYRICS ON STUDENTS’ ENGLISH PHRASAL VERBS MASTERY - Nadia Suryandari; Fakhri Ras; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objective of this study is to get the empirical data about the effect of using song lyrics on students’ English phrasal verbs mastery one ten graders of SMK Perpajakan Riau especially in X Banking class. The method used in this thesis was a quantitative method using pre-experimental design. This study used all of the tenth-grade students of SMK Perpajakan Riau. The sampling technique used in this study was simple random sampling. The sample of this study was X Banking A of class consist of 32 students. In collecting data, the writer conducted a post-test about the phrasal verb using song lyrics test. The test consisted of 20 multiple choices and 10 matching words. In this research, there were six meetings for treatments including a pre-test and a post-test that used the song lyrics as the main subject for learning phrasal verbs in the class. It was found that mean scores of the pre- test and the post-test were 40.6931 and 82.4175 consecutively. The difference of the mean score between the pre-test and the post-test was 41.72. The gap of the mean score showed a significant effect of students’ phrasal verb mastery test.Keywords: Effect, Song lyrics, English Phrasal Verbs